Study about Imperialism, its Origins and Consequences - Kumar, Parveen (Innovative Research Thoughts, 2018)
The word impérialiste was originally coined in France in the 1830s to denote a partisan of the one-time Napoleonic empire (Koebner & Schmidt 1964). “Imperialism” soon developed into a term of abuse employed before 1848 to castigate the Caesar-istic pretensions of Louis Napoleon. It was later used in a similar way both by French opponents of Napoleon III and by British adversaries of French rule and expansionism. In the 1870s British antagonists of Disraeli began to use the word as a domestic invective. But other British writers and politicians sought to rehabilitate the term. They applied it first to the policy of establishing a “Greater Britain” (Dilke 1869), through “the expansion of England” (Seeley 1883) into an “imperial federation” of Britain, its overseas settlements, and India. The acquisition of a large colonial empire in Asia and Africa led to the view that it was the “white man’s burden” (Kipling) to assume a “dual mandate” (Lugard 1922) for offering civilization to “backward” peoples and for opening their territories for the benefit of the world. Thus the term became increasingly identified with British colonialism.